Humans shape the year‐round distribution and habitat use of an opportunistic scavenger. Issue 11 (15th April 2020) - Ramírez, Francisco; Afán, Isabel; Bouten, Willem; Carrasco, Josep Lluís; Forero, Manuela González; Navarro, Joan
Abstract: Research focused on evaluating how human food subsidies influence the foraging ecology of scavenger species is scarce but essential for elucidating their role in shaping behavioral patterns, population dynamics, and potential impacts on ecosystems. We evaluate the potential role of humans in shaping the year‐round distribution and habitat use of individuals from a typical scavenger species, the yellow‐legged gull ( Larus michahellis ), breeding at southwestern Spain. To do this, we combined long‐term, nearly continuous GPS‐tracking data with spatially explicit information on habitat types and distribution of human facilities, as proxied by satellite imagery of artificial night lights. Overall, individuals were mainly associated with freshwater habitats (mean proportion, 95% CI: 40.6%, 36.9%–44.4%) followed by the marine‐related systems (40.3, 37.7%–42.8%), human‐related habitats (13.5%, 13.2%–13.8%), and terrestrial systems (5.5%, 4.6%–6.5%). However, these relative contributions to the overall habitat usage largely changed throughout the annual cycle as a likely response to ecological/physiological constraints imposed by varying energy budgets and environmental constraints resulting from fluctuations in the availability of food resources. Moreover, the tight overlap between the year‐round spatial distribution of gulls and that of human facilities suggested that the different resources individuals relied on were likely of anthropogenic origin. We therefore provide evidence supporting the high dependence of this species on human‐related food resources throughout the annual cycle. Owing to the ability of individuals to disperse and reach transboundary areas of Spain, Portugal, or Morocco, international joint efforts aimed at restricting the availability of human food resources would be required to manage this overabundant species and the associated consequences for biodiversity conservation (e.g., competitive exclusion of co‐occurring species) and human interests (e.g., airports or disease transmission). Abstract : We investigate the spatial distribution and habitat associations of a yellow‐legged gull population inhabiting a highly anthropogenic landscape, and throughout a complete annual cycle. The tight overlap between the spatial distribution of gulls and that of human facilities (as proxied by satellite imagery of artificial night lights) supports the high dependence of this species on human‐related resources. Gulls relied differently on different types of human food subsidies throughout the annual cycle as evidenced by observed changes in habitat use.